Inhibition of renin-angiotensin system attenuates type I alveolar epithelial cell necroptosis in rats after hyperbaric hyperoxic exposure - Han, CuiHong; Zhang, PeiXi; Liu, Ying; Xu, JiaJun; Yu, XuHua; Wen, YuKun; Wang, ShiFeng; Liu, WenWu (Frontiers in Medicine, 2025)
ObjectiveThere is evidence showing both necroptosis and activation of renin-angiotensin system (RAS) are involved in the pathogenesis of hyperbaric hyperoxic lung injury (HLI). This study aimed to investigate whether RAS activation can induce lung cell necroptosis and the cell specificity of necroptosis in the lung in case of hyperbaric HLI.MethodsMale SD rats were randomly assigned into control group (n = 12), HLI group (n = 18), captopril group (n = 18), and valsartan group (n = 18). Rats were pre-treated with intraperitoneal captopril (50 mg/kg) or intragastrical valsartan (30 mg/kg) for 3 days before hyperbaric exposure. Then, animals were exposed to 99.9% oxygen at 250 kPa for 6 h to induce HLI. After hyperbaric exposure, lung function was non-invasively detected, and then animals were sacrificed for the detection of wet to dry ratio of the lung, blood gas and lung inflammatory factors, and lung tissues were collected for double immunofluorescence staining. Statistical analysis was performed with one way analysis of variance.ResultsEither valsartan or captopril pre-treatment could inhibit lung edema, improve blood gas (0 h) and lung function (48 h), and reduce pro-inflammatory factors in the lung. In addition, valsartan or captopril pre-treatment could inhibit AGT1 expression and lung cell necroptosis, and type I alveolar epithelial cells (AECs) were the major cell type experiencing necroptosis after hyperbaric hyperoxic exposure.ConclusionOur study indicates inhibition of RAS can suppress the hyperbaric HLI, which may be, at least partially, related to the inhibition of type I AECs necroptosis. Our findings provide new mechanism for the protective effects of RAS inhibition on hyperbaric HLI.